Film, Philosophy, and Intercultural Film Criticism - Ženko, Ernest (Filozofski vestnik, 2019)
Film, contrary to the other “traditional” arts that have been developing over centuries, is a creation of modern times, and when it emerged it was not only a modern technological achievement but also a medium intended for the masses. Torn between art and popular entertainment, from its very beginning film was a source of oppositions, dichotomies, and fierce struggles. Some oppositions exist on the level of production, others on the level of reception, and above all they are present in the field of film criticism, which itself is split between journalistic criticism and the more philosophically and theoretically informed academic variety. This essay focuses on intercultural film criticism and scrutinises different variations of its relationship with philosophy and points out that so-called “classical” film criticism, based on psychoanalysis, semiotics, and Marxism, as well as film criticism of the “analytic-cognitivist” variety, cannot properly address this topic. It also shows that the approach developed by Fredric Jameson offers a much more adequate option, which not only addresses the film medium in the geopolitical context, but also enables, through film, an understanding of contemporary global society.